Impact of coronary anatomy and residual syntax score on arrhythmic events in patients with ischemic cardiomyopathy. (19th May 2022) - Meynet, I; Quadri, G; Tricomi, L; Tomassini, F; Rolfo, C; Franze', A; Zanda, G; Piedimonte, G; Minniti, D; Varbella, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: ICD implantation is a cornerstone for primary prevention in patients with ischemic cardiomyopathy and impaired left ventricular function; reduced ejection fraction alone, however, doesn't seem enough to discriminate which patients will really experience arrhythmic events in the follow up. Purpose: We hypothesized that coronary anatomy and the extent of residual coronary lesions, measured with syntax score, could be a better predictor of the outcome in this setting. Materials and method: Data of all patients implanted with single or dual chamber ICD in primary prevention for ischemic cardiomyopathy from 2011 to 2020 were retrospectively collected, together with follow up data obtained from clinical visits and ICD remote monitoring. Residual syntax score (RSS) was calculated for each patient, taking into consideration the last coronary angiography performed before ICD implantation. Results: 110 patients were included in our registry. 90.1% were male, mean age was 66±7 years. 23.6% ICD were dual chamber devices. 96 (87.2%), 8 (7.3%) and 6 (5.5%) patients presented respectively with low (0-22), intermediate (23-32) or high (≥33) RSS. After a mean follow up of 4.4±2.9 years, 31 patients (28.2%) died; 20 patients (18.2%) and 27 patients (24.5%) received any appropriate ICD therapy, either shock or ATP. 12 patients (10.9%) experienced inappropriate shock. The composite outcome of death or any appropriate therapy (MACE) was observed in 47 patients (42.7%); left main or left descending artery stenosis were predictors of MACE (p = 0.026 and p = 0.040, respectively). Intermediate or high RSS was the only predictor of appropriate shock (p = 0.046). Conclusions: Coronary anatomy and residual coronary stenosis quantified with syntax score are promising predictors of arrhytmic events during the follow up in patients with ischaemic cardiomyopathy and ICD implanted in primary prevention.